ATTRIBUTES OF EPILEPSY IN CHILDREN FROM THE CITY OF TYUMEN AND THE SOUTHERN PART OF TYU MEN REGION - S.V. Neustroeva; E.V. Levitina ("Paediatrician" Publishers LLC, 2006)
The study included 600 children and adolescents with epilepsy who live in the city of Tiumen and in the southern part of Tiumen region. The clinical and statistical data along with the results of EEG and neurivisualization methods were used to estimate the attributes of epilepsy in children from the city of Tiumen and the southern part of Tyumen region - the clinical course, neuroa physiologic signs and symptoms and unfavorable predictors. The obtained data provided basis for the carried out assessment of efficacy of different treatment methods. Key words: epilepsy, EEG, adolescents, attributes.